Evaluation of the effect of the child protection act on serious child physical abuse in Taiwan. (September 2019) - Chou, I-Jun; Kong, Shu-Sing; Chung, Ting-Ting; See, Lai-Chu; Kuo, Chang-Fu; Lin, Jainn-Jim; Wang, Huei-Shyong; Lin, Kuang-Lin; Hung, Po-Cheng; ,
Abstract: Background: Few studies have examined the effects of the Child Protection Act on child maltreatment in Taiwan. Objective: This study estimated the secular trends in the incidence rate of physical abuse of children requiring hospitalization between 1996 and 2013, and the subsequent in-hospital death proportion before and after implementation of the Act in 2003. Participants and setting: The cases were children younger than 12 years old who were hospitalized due to child abuse, shaken-baby syndrome, neglect, or homicide between 1996 and 2013. A comparison group consisted of children requiring hospitalization for other reasons. We used the National Health Insurance database to identify patients. Methods: The Joinpoint Regression Program was used to estimate temporal trends in the standardized incidence rates. Results: Between 1996 and 2013, 2050 children required hospitalization for physical abuse. Before 2005, the annual percent change increased by 9.40 [95% confidence interval (CI), 4.98–14.00] per year, and after 2005 the annual percent change was –4.80 (95% CI, –9.53–0.17) per year. Among the 2050 physically abused children requiring hospitalization, 83 (4%) died in hospital. The in-hospital death proportion was 2.62% before 2003 and 4.90% after 2003, and the ratio of these two proportions was 1.43 (95% CI, 0.80–2.58). Conclusions: The trend in the incidence of hospitalization of children due to physical-abuse-related injuries started to decline 2 years after implementation of the Child Protection Act. However, the proportion of children who died in hospital as a result of physical abuse requiring hospitalization did not change.